ANALISIS PERMINTAAN DAGING SAPI POTONG DI PROVINSI SUMATERA SELATAN - Oktariani, Lisna (Universitas Muhammadiyah Palembang, 2017)
This research aims are to analyze production growth of beef in South Sumatra, to analyze behavior description of demand factors of beef in South Sumatra, to analyze response of factors that affect demand of beef in South Sumatra. This research used historical method. The data are analyzed in the model of econometrics and are processed with 2 SLS mode and followed by elasticity analyze. The results indicated that : 1) the development of beef production in South Sumatera continues to increase, despite it has not been able to fulfill all of beef demand in South Sumatera, 2) the factors that affect the demand of beef in South Sumatra are price of chicken meat, income in South Sumatera, and lagged demand of beef in South Sumatera, 3) In short-term, income is inelastic where the change in income is not responsive to the beef demand. This is due increase in income has not been able to increase their purchasing power. In long-term changes in income are responsive. Population changes in both the short-term and long-term are responsive to beef demand. It is because beef is not a staple food therefore population growth will cause the population to reduce the demand for food thatis not a staple food.